Analysis of Students' Mathematical Problem-Solving Ability Judging from their Interests - Niswatun Hasanah; Bhaskoro Prasetyo Adi Maryanto; Siti Inganah (WACANA AKADEMIKA: Majalah Ilmiah Kependidikan, 2022)
Mathematical problem-solving ability is one of the most important mathematical abilities and must be possessed by every student. In solving mathematical problems, everyone has a different way and style of thinking. The existence of grouping of students based on the specialization of the special subjects of the department shows that the basic abilities, skills, or intelligence in schools also vary. This study aims to describe students' mathematical problem-solving abilities in terms of specialization in Science, Social Sciences, Language, and Religion with a focus on the Three Variable Linear Equation System (SPLTV). The type of this research is descriptive qualitative analysis research. The subjects in this study were students of class X MAN 2 Malang City. The results of this study indicate that 1) At the stage of understanding the problem, some students with specialization in Social Studies and Language Studies were not able to understand the problem correctly based on the information obtained from the problems given, 2) At the stage of implementing the plan students with specialization in Religion Studies, Social Studies, and Language Studies made several mistakes such as lacking careful in carrying out arithmetic operations so that the results obtained are less precise, 3) At the stage of re-examining students with specialization in Religion Studies and Language Studies, they do not write down the results of re-checking because they are not accustomed to re-checking whether the answers obtained are correct or not, 4) Students with specialization Science Studies has fulfilled every stage of problem-solving